A study of the compliance of selected barangays in Quezon City to relevant laws and regulations on archives and records management - Juanson, Vivian Sarah C. (2012)
This study was conducted to find out the extent of compliance of the 14 out of 15 selected barangays in Quezon City to the relevant laws, rules and regulations on archives and records management. The following specific objectives were: 1) to determine how many barangays have separate archives and records offices, existing archival systems, policies and practices on archives and records management; 2) to find out the practices of the barangays regarding records storage and maintenance; 3) to know the policies and practices of the barangays regarding the disposal of different barangay records; 4) to determine how many barangays have Records Officers, their responsibilities, duties and practices on archives and records management and to find out the responsibilities and duties of the barangay secretaries, Treasurers and Heads regarding archives and records management and; 5) to come up with recommendations that will improve the existing status of archives and records management of the barangays and their compliance with the laws and regulations.